2018
DOI: 10.3389/fpsyg.2018.00476
|View full text |Cite
|
Sign up to set email alerts
|

Null tDCS Effects in a Sustained Attention Task: The Modulating Role of Learning

Abstract: The purpose of this study was to investigate sustained attention through modulation of the fronto-cerebral network with transcranial direct current stimulation (tDCS) in adults with attention-deficit/hyperactivity disorder (ADHD) and control participants. Thirty-seven participants (21 with ADHD) underwent three separate sessions (baseline, active tDCS, and sham) and performed the MOXO Continuous Performance Test (CPT). We applied double anodal stimulation of 1.8 mA tDCS for 20 min over the left and right dorso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 59 publications
1
48
1
Order By: Relevance
“…However, they are less unusual than one may think. In fact, they were observed by Jacoby and Lavidor [82] during a sustained attention task, by Hammer, Mohammadi, Schmicker, Saliger, and Münte [83], who observed decreased memory performance in a cathodal condition compared to sham tDCS but only after learning and by Zaehle et al [84], who suggested that performance enhancement due to task repetition might be hampered by cathodal stimulation over the lDLPFC. Our findings of reduced interference from angry distractor-faces indicate the other side of the coin: namely, that performance enhancement due to task repetition is potentiated by anodal stimulation of the lDLPFC/cathodal rPPC.…”
Section: Discussionmentioning
confidence: 89%
“…However, they are less unusual than one may think. In fact, they were observed by Jacoby and Lavidor [82] during a sustained attention task, by Hammer, Mohammadi, Schmicker, Saliger, and Münte [83], who observed decreased memory performance in a cathodal condition compared to sham tDCS but only after learning and by Zaehle et al [84], who suggested that performance enhancement due to task repetition might be hampered by cathodal stimulation over the lDLPFC. Our findings of reduced interference from angry distractor-faces indicate the other side of the coin: namely, that performance enhancement due to task repetition is potentiated by anodal stimulation of the lDLPFC/cathodal rPPC.…”
Section: Discussionmentioning
confidence: 89%
“…Finally, we used jackknife sensitivity analyses (i.e., repeating the same analysis and excluding a different study each time) to establish the replicability of findings. To improve homogeneity, we carried out additional sensitivity analyses that excluded studies with overlapping samples, [60][61][62][63] or studies with methods that deviated from the majority of studies, such as those including community participants with high ADHD symptoms on validated ADHD ratings scales but without a clinical ADHD diagnosis; 43,64 those including adult samples with ADHD; 42,65,66 those targeting the right inferior frontal cortex (IFC); 43,67 those reporting change scores (i.e., post minus pre differences) rather than post scores only; 66 those using multi-stimulation sessions; [60][61][62]65 those with effect sizes based on working memory or WCST tasks; 61,68 or those using parallel rather than crossover designs. 62,66,67 Lastly, given that effect-size estimates might be inflated in studies with a high risk of bias, we conducted meta-regression analyses to compare the effect sizes of studies with high versus low or unclear risk of bias for each risk of bias domain (i.e., selection bias, performance bias, detection bias, attrition bias and other biases).…”
Section: J Psychiatry Neurosci 2021;46(1)mentioning
confidence: 99%
“…Cosmo et al 66 None reported Jacoby et al 42 Not tested, but authors reported that stimulation was well tolerated and no side effects were reported Munz et al 60 Not tested, but no side effects were reported Nejati et al 68 Reports of mild itching or tingling under electrodes Paz et al 73 Allenby et al 65 Bloch et al 71 rTMS studies tDCS studies…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This level of analysis, therefore, is optimal for explaining disorders based on neurological problems and brain injuries. There has been prolific evidence in recent years of the important role of the frontal cortex and the functional role of “executive functions” for predicting performance (Gathercole and Pickering, 2000a, b; Blair and Razza, 2007; Bull et al, 2008; Cleary and Chen, 2009; Agostino et al, 2010; Molfese et al, 2010; Monette et al, 2011; De los Ángeles, 2012; Diamond, 2012, 2013; Ramírez, 2014; Arán and López, 2016; Diamond and Ling, 2016; Cid-Sillero et al, 2018; Díez and Bausela, 2018; Follmer, 2018; Jacoby and Lavidor, 2018). An impairment in executive functioning has also been related to antisocial and delinquent behaviors (De Brito and Hodgind, 2009; Pera-Guardiola et al, 2016; Gil-Fenoy et al, 2018).…”
Section: The Case Of Executive Functions Self-regulation and Externmentioning
confidence: 99%